A Critical Theory Perspective On Employer Branding Dilemmas in Traditional Companies Attracting Gen Z Talent in the Gig Economy - Kurniawan, Agung Widhi (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The gig economy has disrupted traditional employment models, creating significant challenges for conventional companies in attracting Generation Z (Gen Z) talent. This study examines employer branding dilemmas through a Critical Theory lens, exploring power dynamics, structural inequalities, and ideological conflicts between traditional corporate structures and Gen Z's work preferences. Using qualitative data from Focus Group Discussions (FGDs) with HR professionals and Gen Z freelancers, the research reveals a fundamental mismatch between traditional employer value propositions (job stability, hierarchical growth) and Gen Z's expectations of flexibility, purpose-driven work, and digital-first engagement. Findings highlight systemic contradictions in corporate attempts to reconcile rigid structures with gig economy appeal. The study recommends rethinking employer branding narratives to align with Gen Z's critical perspectives on labor markets, proposing hybrid models that blend security with autonomy. This research contributes to ongoing debates about sustainable talent acquisition in evolving economic landscapes.